Optimization of ultrasonication assisted extraction of Aegle marmelos fruit shell nano polysaccharide and evaluation of photocatalytic dye reduction and edible coating for fresh-cut fruits - Madhu Sharma; Aarti Bains; Gulden Goksen; Nemat Ali; Mohammad Rashid Khan; Gulsah Karabulut; Prince Chawla (Food Chemistry: X)
Aegle marmelos (AM) fruit shell, considered waste, is an excellent source of bioactive compounds, including polysaccharides. Therefore, this study focuses on the extraction of AM polysaccharides using an ultrasonication-assisted approach. Different parameters, including ultrasonic power (200–600 W), time (5–15 min), and solid-to-solvent ratio (10–20 mg/mL), were employed, and significantly (p < 0.05) higher yield (16.93 %) was achieved at 400 W for 10 min. Monosaccharides composition revealed galactose (30.56 ± 0.76 %), galacturonic acid (24.72 ± 0.12 %), arabinose (17.26 ± 0.35 %), xylose (11.48 ± 0.21 %), glucose (10.52 ± 0.26 %), and rhamnose (5.39 ± 0.67 %), which were then confirmed by 13C spectrum. AM polysaccharides revealed nanoscale size with excellent structural crystallinity and thermal stability. Edible coatings of varying concentrations (0.5–2 %) were formulated and optimized 1 % coating, demonstrating efficacy in mitigating weight loss, microbial proliferation, and browning in cut apples. As well, AM polysaccharides prominently degraded 82.79 ± 0.39 % of methyl green. Overall, bael shells as a valuable source of polysaccharides, offering the potential for both photocatalytic dye degradation and food preservation.